(untitled) (Majalah Kedokteran Bandung, 2026)
Tuberculosis (TB) is an infectious disease that poses a substantial public health challenge in developing countries, including Indonesia. Children under five years of age show increased susceptibility to the infection due to incompletely developed immune systems. Therefore, this study aimed to determine the relationship between TB risk factors and pulmonary TB incidence among children aged 0–5 years seen at Panti Abdi Dharma Hospital, Cirebon, Indonesia. A cross-sectional design was used with a sample of 196 children visiting the pediatric outpatient clinic at Panti Abdi Dharma Hospital from February-April 2025. Data were collected using a stuctured questionnaire that includes variables of age, gender, nutritional status, BCG vaccination history, exclusive breastfeeding history, birth weight, history of contact with TB patients, parents’ education and occupation, family smoking behavior, and housing density. Univariate analysis results showed that most respondents were >2–5 years old (50.5%) and predominantly male (53.6%). Chi-square tests showed significant associations between age, nutritional status, and a history of contact with adult TB patients and pulmonary TB incidence (p<0.05). Multivariate logistic regression showed that nutritional status and history of contact with adult TB patients were significant predictors of pulmonary TB. Good nutritional status was identified as a protective factor (OR=0.276; p<0.001), with children with poor or inadequate nutritional status had approximately 3.62-fold higher odds of developing TB compared with those with good nutritional status. In conclusion, poor or inadequate nutritional status and a history of contact with adult TB patients are the most influential risk factors for pulmonary TB among children aged 0–5 years at Panti Abdi Dharma Hospital, Cirebon, Indonesia.